Mechanical pinprick pain in patients with unilateral spatial neglect: The influence of space representation on the perception of nociceptive stimuli. (15th December 2016) - Vizzari, V.; Barba, S.; Gindri, P.; Duca, S.; Giobbe, D.; Cerrato, P.; Geminiani, G.; Torta, D.M.
Abstract: Background: Crossing the hands over the midline can reduce the perceived intensity of nociceptive stimuli applied onto the hands. It remains unclear to what extent intact representation of peripersonal space influences this effect. Here we used the crossed‐hands paradigm in patients with unilateral spatial neglect, a neuropsychological condition characterized by the inability to detect, attend and respond to contralesional (most often left) stimuli, and spared ability to process stimuli in the non‐affected space. Methods: Sixteen post‐stroke patients without unilateral neglect and 11 patients with unilateral spatial neglect received punctate mechanical pinprick stimuli onto their crossed or uncrossed hands. We tested: (i) whether deficits in space representation reduce the possibility of observing 'crossed‐hands analgesia', and; (ii) whether placing the contralesional hand, normally lying in the affected space in the healthy space would increase the number of detected stimuli. Results: Our results showed that neglect patients did not exhibit 'crossed‐hands' analgesia, but did not provide strong evidence for an improvement in the number of detected stimuli when the contralesional hand was in the healthy space. Conclusion: These findings uphold the notion that the perception of nociceptive stimuli is modulated by the relative position of the hands in space, but raise questions about the conditions under which these effects may arise. Significance: We show that deficits in space representation can influence the processing of mechanical pinprick stimuli. Our results raise several questions on the mechanisms underlying these effects, which are relevant for the clinical practice.